Communicative compathy and chronic care - Sanjay Kalra; Chitra Selvan; Suneet Kumar Verma (Journal of the Pakistan Medical Association, 2023)
The concepts of sympathy and empathy are well entrenched in social and medical literature. In this article, we explore a relatively less explored construct, compathy. Compathy, defined as feelings that are shared with others, is a higher level of emotional maturity, which helps in achieving better quality care. We propose further discussion and debate on how to measure, attain, and maintain compathy in chronic care practice. Keywords: Care giver health, chronic disease, communication, diabetes, person centred care.